SISTEM INFORMASI PEMASARAN PT TELKOM DIVISI FIXED WIRELESS UNTUK PERENCANAAN PROGRAM DAN MENAMPILKAN INDIKATOR PERFORMANSI PEMASARAN - Kus Indartama; Aries Tjahyanto (Jurnal Teknobisnis, 2005)
In today’s business environment, information technology plays an important role in supporting firms to achieve their business objectives including marketing management. The provision of accurate data in a timely manner is important to support planning and monitoring marketing performance. Planning a structured and integrated marketing plan requires involvement from various divisions including Sales, Tariff, Service, Legal, Finance, Information Systems, Billing and Product Owner. In order to measure marketing performance following the commencement of a program, demonstration of marketing performance indicators quickly and accurately is necessary. This study aims to develop an information system to support the marketing program planning process and show marketing performances indicators online.The scope of information systems developed is PT Telekomunikasi Indonesia Fixed Wireless Division. The users of the information systems are divisions or units related to marketing management. Development stage starts with a survey and establishment of user requirement until design stage. Methods used in this study are interviews, survey, literature, review and focus group discussion followed by data requirement analysis and system design.The benefits of the system developed in this study are increasing efficiency and effectiveness of program planning and marketing performance measure, as well as increasing management control of marketing performance.Results obtained from this study are the establishment of user requirements in program planning process and the development of a feasible information system from technical, operational and economic point of views. Further investigation and design in a national scope are required to establish a national system, followed by implementation, testing and deployment to apply the information system.